Outreach and Profitability Trade-off: Does Synergy between Islamic Banking and Islamic Microfinance Institutions Matter? - Nasution, Ruri Eka Fauziah; Ahmed, Habib (UI Scholars Hub, 2015)
The purpose of this study is to examine the effectiveness of linkage program between Islamic Banking (IB) and Baitul Maal Wat Tamwil (BMT) on BMT financing growth and profitability. This study also aims to compare three linkage models and to explore the keys factors that affect the implementation of linkage program. To achieve these objectives, both quantitative and qualitative research methods are employed. The dataset consists of the financial statement of 26 BMT in Indonesia and interviews with 12 managers of BMT and IB in Jakarta. The findings suggest that a synergy between IB and BMT through linkage program has significant impact on BMT financing growth and BMT ROE. Among three linkage models, executing model appears to be the most preferable model, both by BMT and IB. The finding also suggests that internal and external factors at BMT level have impacts on the effectiveness of linkage program.